5‐Formylcytosine and 5‐Carboxylcytosine Significantly Reduce the Catalytic Activity of Hhal DNA Methyltransferase. Issue 6 (12th May 2017) - Hong, Tingting; Wu, Fan; Fu, Boshi; Yuan, Yushu; Xu, Jinglei; Wang, Tianlu; Zhou, Xiang
Abstract: DNA methylation is an essential epigenetic modification, and found to be dynamically changed due to the observation of active DNA demethylation. During active demethylation, 5‐methylcytosine (5mC) was oxidized stepwise by ten‐eleven translocation (TET) enzymes into 5‐hydroxymethylcytosine (5hmc), 5‐formylcytosine (5fC), and 5‐carboxylcytosine (5caC). Then, the subsequent excision of 5fC and 5caC combined with base excision repair further restored cytosine, which completes the demethylation process. Here, we report that 5‐formylcytosine and 5‐carboxylcytosine significantly reduce the activity of HhaI DNA methyltransferase to methylate target cytosines when present on the hemi‐modified sequence of the complementary DNA. This finding demonstrates that 5fC and 5caC function as more than intermediates for active DNA demethylation. Abstract : 5‐Formylcytosine and 5‐carboxylcytosine can significantly reduce the catalytic activity of HhaI DNA methyltransferase among the five cytosine derivatives involved in active demethylation.